(untitled) (Global Journal of Human-Social Science, 2019)
The present study has been done by using webometric methods. Each Social Media web site was searched in Alexa databank and relevant data including traffic rank, pages viewed, links, bounce percentage, time on site, search percentage, and Indian/other users were collected. Social media has become something that is important to enhance social networking and sharing of information through the website. Social media have not only changed social networking, they provide a valuable tool for social organization the website of a Social Media Sites is a platform to exhibit the courses offered by the institution and also about the research activities carried out by that Social Media Site. Prioritizing the content is one of the best ways to make sure the visitors are finding the information the site wants them to find, and that they wants to find, and that they want to find. a total of 64 Popular Social Media Sites were taken up for the study homepage of the Social media were taken up for the study and the various web objects were identified and also their locations in the home page of the Social Media Sites were analyzed and discussed. The study also helps the web designers to improve the usability of websites.